Rhyme Awareness in Children With Normal Hearing and Children With Cochlear Implants: An Exploratory Study - Jing, Linye; Vermeire, Katrien; Mangino, Andrea; Reuterskiöld, Christina (Frontiers in Psychology, 2019)
Phonological awareness is a critical component of phonological processing that predicts children’s literacy outcomes. Phonological awareness skills enable children to think about the sound structure of words and facilitates decoding and the analysis of words during spelling. Past research has shown that children’s vocabulary knowledge and working memory capacity are associated with their phonological awareness skills. Linguistic characteristics of words, such as phonological neighborhood density and orthography congruency have also been found to influence children’s performance in phonological awareness tasks. Literacy is a difficult area for deaf and hard of hearing children, who have poor phonological awareness skills. Although cochlear implantation (CI) has been found to improve these children’s speech and language outcomes, limited research has investigated phonological awareness in children with CI. Rhyme awareness is the first level of phonological awareness to develop in children with normal hearing (NH). The current study investigates whether rhyme awareness in children with NH (n = 15, median age = 5; 5, IQR = 11 ms) and a small group of children with CI (n = 6, median age = 6; 11.5, IQR = 3.75 ms) is associated with individual differences in vocabulary and working memory. Using a rhyme oddity task, well-controlled for perceptual similarity, we also explored whether children’s performance was associated with linguistic characteristics of the task items (e.g., rhyme neighborhood density, orthographic congruency). Results indicate that there is an association between vocabulary and working memory and performance in a rhyme awareness task in NH children. Only working memory was correlated with rhyme awareness performance in CI children. Linguistic characteristics of the task items, on the other hand, were not found to be associated with success. Implications of the results and future directions are discussed.